Evaluation of Immunization Efficacy for Cell Wall Fraction Antigen Separated from Clinical Isolate of Candida albicans - Abbas, Nada Fadhil; Shani , Wafaa Sadoon; Alrubyae, Inaam M. (Technium BioChemMed, 2021)
Objective: Preparation of cell wall fraction (CWF) antigen from Candida albicans and testing immunization efficiency by evaluating the humoral immune response (by measuring IgG level in serum) and cellular immune response (by measuring IFN-? and IL4 concentration). Methods: C. albicans were isolated from woman with vaginal candidiasis and identified morphologically and genetically, first cultured on Sabouraud Dextrose Agar (SDA) and CHROMagar Candida media and identified by biochemical test. Then identified by molecular diagnosis by using ITS1 and ITS4 primers. BalB/c mice were immunized subcutaneously and intradermaly with C. albicans strain M366B cell wall fraction antigen for 21 days to evaluate humoral and cellular immune response represented by IgG, Th1 and Th2 cytokine level by microtiterplate ELISA. Results: IgG level appeared in high concentration in immunized mice by comparison with control groups in a high significant differences (P<0.01), and immune response represented by (IL-4) concentration in immunized group was higher than those in control mice in a significant differences (P<0.01); while there was significant decreasing in (IFN-?) concentration in mice injected subcutaneously and intraderamly by comparing with control groups. So CWF antigen can efficiently stimulate both humoral and cellular immune response by elevation both IgG and IL-4 concentration in sera of immunized mice. Conclusions: CWF antigen was immunogenic in regarding in inducing IgG and IL-4 secretion.